2008
DOI: 10.4141/cjas07082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monensin on beef cow reproduction

Abstract: , with or without grain supplementation, shortened the period from calving to conception and increased calving percentage in beef cows consuming bermudagrass hay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…A implementação de programas de suplementação direcionados a vacas de corte durante os períodos pré-parto e/ou pós-parto pode ser considerada uma estratégia vantajosa para otimizar a eficiência nutricional em sistemas de pastejo, especialmente quando se faz uso de suplementos proteicos (Delcurto, 2000). Além disso, a implementação de estratégias dirigidas ao aumento das concentrações de glicose e insulina no plasma sanguíneo, tais como a inclusão de monensina na dieta, pode potencialmente contribuir para a melhoria dos efeitos reprodutivos (Bailey, 2008;Hardin, 1983).…”
Section: Introductionunclassified
“…A implementação de programas de suplementação direcionados a vacas de corte durante os períodos pré-parto e/ou pós-parto pode ser considerada uma estratégia vantajosa para otimizar a eficiência nutricional em sistemas de pastejo, especialmente quando se faz uso de suplementos proteicos (Delcurto, 2000). Além disso, a implementação de estratégias dirigidas ao aumento das concentrações de glicose e insulina no plasma sanguíneo, tais como a inclusão de monensina na dieta, pode potencialmente contribuir para a melhoria dos efeitos reprodutivos (Bailey, 2008;Hardin, 1983).…”
Section: Introductionunclassified
“…Studies have shown that supplemental protein for beef cattle grazing low-quality forage has a positive effect on increasing forage intake, body weight (BW), BCS, blood metabolites and reproductive efficiency [ 13 , 16 ]. Furthermore, strategies to increase blood glucose and insulin concentrations, such as feeding monensin, could enhance reproductive outcomes [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%